Gender mainstreaming in Nordic development agencies: Seventeen years after the Beijing conference - Malokele Nanivazo; Lucy Scott (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
The Fourth World Conference on Women, held in Beijing in 1995, was critical in making gender equality a development goal and adopted gender-mainstreaming as its primary mechanism to achieve this. Effective implementation of gender-mainstreaming involves changing both the internal organization and the external operations of development agencies to ensure that gender is integrated throughout the life cycle of all policies, programmes and practices. This paper assesses gender-mainstreaming in the development co-operation strategies and activities of three Nordic countries - Denmark, Finland, and Sweden - in two aspects. The first aspect focuses on the central level of development agencies in terms of strategies, operations, and structures while the second component examines gender-mainstreaming at the embassy level, in terms of gender-mainstreaming in implementation and interventions for advancing gender equality.
Keywords: F35; 330; gender; gender mainstreaming; development agencies; Beijing conference